2020
DOI: 10.35848/1347-4065/aba6fd
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Cu-doped thin Ge film assisted with a Cu–Ge droplet

Abstract: We observed the crystallization process of an amorphous germanium (a-Ge) thin film, including copper (Cu) nanoparticles in the intermediate position of the structures in terms of depth, by using in situ TEM. It was found that a nanoscale droplet was formed around the Cu nanoparticles at 500 °C, which is lower than the eutectic temperature of the bulk Cu-Ge system (640 °C); following which, the nanoscale droplets solidified at the same temperature. The existence of a nanoscale liquid phase at a temperature lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The composition of Cu in the film with t Cu = 4 s was estimated to be approximately 0.1 from the SIMS profile in which the Cu atoms diffused from the middle to both Ge/ insulator interfaces; excessive atoms were gettered by the strain field around the defects. 25,26) These results indicate that the optimal value of t Cu exists below 1 s; that is, the suppressive supply of Cu (less than a few at% of Ge) is effective for enhancing the progress of MIC. Furthermore, it played a role in reducing the transition from the amorphous state to the nano-sized crystallite state, which was considered in the sputtering films.…”
Section: Progress Of Spc and Micmentioning
confidence: 84%
See 2 more Smart Citations
“…The composition of Cu in the film with t Cu = 4 s was estimated to be approximately 0.1 from the SIMS profile in which the Cu atoms diffused from the middle to both Ge/ insulator interfaces; excessive atoms were gettered by the strain field around the defects. 25,26) These results indicate that the optimal value of t Cu exists below 1 s; that is, the suppressive supply of Cu (less than a few at% of Ge) is effective for enhancing the progress of MIC. Furthermore, it played a role in reducing the transition from the amorphous state to the nano-sized crystallite state, which was considered in the sputtering films.…”
Section: Progress Of Spc and Micmentioning
confidence: 84%
“…Several TEM images and SIMS profiles have been demonstrated in other studies. 11,21,[24][25][26] 3. Results and discussion 3.1.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] To investigate the details of the crystallization mechanism of Cu-MIC, we used Cu sandwiched between Ge as an initial film and performed in situ TEM observation of crystal growth at 500 °C. 25) Cu was found to exist as thin nanodisks with a diameter of several 10 nm immediately after deposition. The research showed that nanodroplets formed around the Cu nanodisks at 500 °C within 5 min, which then solidified.…”
Section: Introductionmentioning
confidence: 99%